Performance analysis of aluminimum oxide/polyalkylene glycol nanolubricant in automotive air conditioning system - Mohamad Redhwan, Abd Aziz (2018)
Energy saving and fuel efficiency enhancement approach will lessen the reliance on fossil fuel. One of the superlative approaches to enhance the fuel efficiency and eventually saving the energy is by improving the performance of the automotive air conditioning (AAC) system. The AAC system is the biggest supplementary load on a vehicle; extra load employed by the AAC system signifies a decrease in efficiency, increase in fuel consumption and escalates the greenhouse gas discharges. The current hot world weathers and El-Nino affects escalate the use of AAC considerably. One of the novel approaches in increasing AAC’s efficiency is by introducing nanoparticles into the refrigeration system. The aim of the present study is to evaluate and optimize the AAC performance and power saving using Aluminium Oxide/Polyalkylene Glycol (Al2O3/PAG) nanolubricants. This can be achieved by stabilizing and characterizing the Al2O3/PAG nanolubricant, investigating the performance and relative power consumption and; finally optimizing the operating parameters of the AAC system. The Al2O3/PAG nanolubricant is prepared by using the two-step method and colloidal stability is evaluated and established by several methods of analyses. Next, the thermophysical properties of Al2O3/PAG nanolubricant up to 1.0% volume concentrations and 30 to 80 °C working temperatures were investigated. Adding to that, the tribological properties of Al2O3/PAG nanolubricant up to 0.3% volume concentrations was also evaluated. The AAC performances and power saving were evaluated in the range of 900 to 2100 rpm compressor speed, 90 to 170 g initial refrigerant charge and 0.006 to 0.014% Al2O3/PAG nanolubricant volume concentrations. The performance of AAC was evaluated by determining the cooling capacity, compressor work, and coefficient of performance (COP). Meanwhile, power saving was evaluated by determining the relative power consumption. The optimization of the AAC parameter was done by the help of statistical tool software employing ANOVA analysis for determining the significant factors and established the relation between the factors. The desirability approach was used in determining the optimal conditions of factors and its responses. The thermal conductivity and viscosity increased with the increase in volume concentrations but decreased with temperature. The tribological properties evaluations found that 0.010% Al2O3/PAG nanolubricant showed optimal conditions with lowest coefficient of friction (COF) and wear rates were achieved. From the outcome of thermophysical and tribological evaluation, the investigation of AAC performances and power saving are evaluated for up to 0.014% volume concentrations only. The results found that the maximum and average COP enhancements are 31.46 and 17.42%, respectively while the highest and average of power saving attained are 23.89 and 11.38%, respectively. Both COP and power saving was highest when 0.010% volume concentration is used. Consequently, the optimization of the parameter namely, compressor speed, initial refrigerant charge and volume concentrations of 1167 rpm, 170 g and 0.011% respectively yield the optimum responses of cooling capacity, compressor work, expansion valve discharge temperature and power saving of 1.303 kW, 14.70 kJ/kg, 4.06 °C and 7.12% respectively with the highest desirability value of 0.819. Finally, it can be concluded that 0.011% volume concentration is the optimum volume concentration. Hence, it is recommended to use 0.011% Al2O3/PAG nanolubricant on to the AAC system for the best performance. Nevertheless, full-blown durability run of AAC system is recommended for future work which is not included in the scope of the present study. New generation of nanolubricant technology AAC system with smaller components and higher efficiency is anticipated in the near future.